Imperfect regeneration analysis of Stirling engine caused by temperature differences in regenerator. (15th February 2018) - Dai, D.D.; Yuan, F.; Long, R.; Liu, Z.C.; Liu, W.
Highlights: A detailed analysis of the regeneration is presented for the first time. The irreversibility caused by temperature differences is considered. The expressions and limits of regenerative effectiveness are obtained. The effects of parameters on the performance of the Stirling engine are studied. Abstract: The Stirling engine has drawn much attention as it can utilize sustainable energy such as solar, waste heat, and biomass. Although the Stirling cycle has the same theoretical efficiency as the Carnot cycle, the thermal efficiency of an actual Stirling engine is lower than that of the ideal Carnot cycle owing to their reversibility. Previous finite-time thermodynamic models of Stirling engines are mainly focused on the temperature difference between the working substance and heat reservoirs. However, there is also a temperature difference between the working substance and the regenerator, which has merely been reported in previous literatures. In this study, we analyzed the regenerative processes of the Stirling engine using finite-time thermodynamics. Using an even distribution temperature assumption, the regenerative effectiveness and its limitations were obtained. For an uneven distribution temperature assumption, the regenerator was modeled by dividing it into n sub-regenerators. Two cases, for either constant or varying temperatures of the sub-regenerators, are discussed in detail, and the same regenerative effectiveness was obtained for the limit n → ∞. Furthermore, the thermal efficiency and output power were obtained, and the effects of the parameters on the performance of the Stirling engine were investigated.